Antiques swap - Allan, Barbara (Allan, Barbara. Trash 'n' treasures mystery., 2015)
"It happened at Serenity's swap meet, right after Brandy Borne and her ever-more-eccentric mother Vivian finished shooting the pilot for their very own TV show, Antiques Sleuths. Brandy just, well lost her balance and fell...into the helpful arms of an old flame, local tycoon Wesley Sinclair III. But did Brandy's innocent slip lead to the murder of Wesley's wife, Vanessa."-- front flap.